2016
DOI: 10.1080/09168451.2015.1116924
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of hydroxytyrosol: a current controversy

Abstract: This study focus on the main factors that affect the antimicrobial capacity of hydroxytyrosol, including the concentration (200, 400, and 1000 μg/mL), target strains, and the culture media (nutrient-rich and less-rich culture media). The potential HT degradation was also evaluated by HPLC-PAD. Kinetic parameters from growth curves showed that HT concentrations produced a doses-dependent shift when compared to the untreated control. In most of the cases, the highest tested dose (1000 μg/mL) was needed to inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 35 publications
2
31
0
Order By: Relevance
“…Hydroxytyrosol (HT), 3,4-dihydroxy phenethyl alcohol, is an important active compound in olive oil and olive leaf [ 1 , 2 ]. Small-molecule HT contains three free hydroxyl groups and presents strong bioactivity, such as antioxidant [ 3 , 4 ], antimicrobial [ 5 , 6 ], and anti-inflammatory properties [ 7 ], in addition to antitumor activity to inhibit the proliferation of human promyelocytic leukemia HL60 cells [ 8 ], human colon cancer HT-29 cells [ 9 ], and MCF-7 human breast cancer cells [ 10 ]. Many works have reported on the HT chemical structure and derivatives [ 11 , 12 ], antitumor activity and mechanism [ 13 ], and pharmacokinetics [ 14 ] for anticancer drugs or cancer adjuvant therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxytyrosol (HT), 3,4-dihydroxy phenethyl alcohol, is an important active compound in olive oil and olive leaf [ 1 , 2 ]. Small-molecule HT contains three free hydroxyl groups and presents strong bioactivity, such as antioxidant [ 3 , 4 ], antimicrobial [ 5 , 6 ], and anti-inflammatory properties [ 7 ], in addition to antitumor activity to inhibit the proliferation of human promyelocytic leukemia HL60 cells [ 8 ], human colon cancer HT-29 cells [ 9 ], and MCF-7 human breast cancer cells [ 10 ]. Many works have reported on the HT chemical structure and derivatives [ 11 , 12 ], antitumor activity and mechanism [ 13 ], and pharmacokinetics [ 14 ] for anticancer drugs or cancer adjuvant therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Olive leaf contains a wide variety of phenolic compounds (Yuan, ), for example, oleuropein (OL), hydroxytyrosol (HT), tyrosol, cumaric acid, ferulic acid, caffeic acid, etc. In particular, small molecule HT presents strong bioactivity, such as antioxidant (Owen, Giacosa, Hull, Haubner, Spiegelhalder, & Bartsch, ; Visioli et al, ), antimicrobial (Bisignano et al, ; Medinamartínez, Truchado, Castroibáñez, & Allende, ), anti‐inflammatory (Killeen, Pontoniere, & Crea, ), antitumor to inhibit proliferation of human promyelocytic leukemia HL60 cells (Fabiani et al, ), human colon cancer HT‐29 cells (Bernini et al, ), and MCF‐7 human breast cancer cells (Bouallagui, Han, Isoda, & Sayadi, ). Many works were reported on HT preparation from natural plant separation and chemical synthesis, but HT yield was very low, and it also need a large amount of toxic agents, expensive catalysts, and long time.…”
Section: Introductionmentioning
confidence: 99%
“…One study reported the antiaging effect of HT [ 41 ]. Three studies focused on investigating the antimicrobial effect of HT [ 42 , 43 , 44 ]. Moreover, eight studies also included the anti-inflammatory effect of HT as a supplementary outcome of their studies [ 32 , 33 , 34 , 35 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%